Primates in Montane Forests of the Región Amazonas, Peru: New Records and the Current Situation of Lagothrix flavicauda and Other Primates - López, Luis [UNESP]; Aquino, Rolando; Guerra-Torres, Llossy N.; Francisco, Talitha Mayumi; Ruiz-Miranda, Carlos Ramon (My University, 2022)
Most of the primate studies in the montane forests of Peruvian Amazonia have been carried out in its northeastern portion, and most have focused on the yellow-tailed woolly monkey, Lagothrix flavicauda. Information gaps remain for much of the forests in this region and the primate species that are found there. Here we report on a survey of L. flavicauda (Critically Endangered) and the White-bellied Spider Monkey Ateles belzebuth (Endangered) and other primates, particularly to assess the status of their populations and identify the anthropogenic threats they face, in the Peruvian Yungas in the northeast of the Región Amazonas. We collected data to estimate abundance in terms of the number of groups detected and their size and location. A preliminary analysis was also carried out to assess anthropic activities that pose threats to the survival of the populations there. The study was conducted from June to August and October 2018. We carried out surveys along line transects and pre-existing trails in three fragments of primary forest in the villages of Flor de la Viña. Cambiopitec and Vista Alegre. In 334 km of surveying, we observed 13 groups of four species. Lagothrix flavicauda was the most frequently sighted (seven groups) and A. belzebuth the least sighted (one group). The other two species seen were the large-headed capuchin Sapajus apella macrocephalus and the Andean white-fronted capuchin Cebus yuracus. Most of the L. flavicauda groups were seen in forests near the village of Flor de la Viña. The single group of A. belzebuth was seen in Vista Alegre. With the exception of Cambiopitec, primates were sighted in extensive forest fragments. The average group size of L. flavicauda was 7.8 individuals (± 4.2; range 4 to 15). For the other species, the numbers of sightings were insufficient to estimate average size. Accordingly, L. flavicauda showed the highest relative abundance 2.42 indiv./10 km and Sapajus a. macrocephalus was the least abundant 0.84 indiv./10 km in Flor de la Viña. Deforestation for agriculture and livestock farming and hunting were the main threats to the survival of these primates. In general, primate richness, the number and size of groups, and the relative abundance that we recorded were similar to those obtained at other sites with similar human activities in the region. The presence of L. flavicauda and A. belzebuth, considered to be the most vulnerable to habitat disturbance, contributed to the local community’s awareness of the importance of forest conservation, mainly in Flor de la Viña. The information obtained on the status of L. flavicauda and other primates will reinforce conservation actions at these sites, particularly Vista Alegre, where there is a Regional Conservation Area. It may also foster other sustainable activities involving the participation of local communities, such as ecotourism and agroforestry.
Keywords: abundance; montane forest; new records; Primates; threats